Descriptive study on the continuing training of Arts teachers of state schools in the capital of Sergipe. - Jorge Luis Santana Luduvice; Luiz Anselmo Menezes Santos; Fabio Kalil de Souza (Universidade Federal de Santa Maria, 2022)
This paper is the result of a Master's dissertation linked to the training of educators research line, at PPGED-UFS[i].The general objective of this study was to describe the position of Arts teachers in the face of their continuing training process. Its specific objectives are: to characterize pedagogical problems with regard to Arts teaching, with emphasis on their origin and how teachers solve them; to understand the connection that these teachers establish with regard to the multivalence of artistic languages; and to relate these issues with the professional life cycle with the aspect of motivation and demand for the realization of the different modalities of continuing training. The research is configured in a qualitative - descriptive approach. The instruments used to collect qualitative data were 30 questionnaires with closed questions and 10 semi-structured interviews. The theoretical basis of this research is organized from the understanding of continuing training as a deontological element of the teaching profession and the characterization of the teaching of the curricular component Arts. The results obtained demonstrate several aspects that may affect the planning of training practices aimed at Arts teachers.